EDUKASI DAN PRAKTEK PEMBUATAN BIODIESEL DARI LIMBAH MINYAK JELANTAH BAGI IBU-IBU MAJELIS TA’LIM AL-HIJRAH DUSUN AIR ALI NEGERI RUMAH TIGA KECAMATAN TELUK AMBON KOTA AMBON - Pagaya, Joseph; Lapu, Petrus; Suriani, Sanita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2024)
Most people, especially in rural areas, do not know the dangers of used cooking oil for health when reused. Used cooking oil that is no longer used should not be thrown into the environment because it can cause environmental pollution (soil and water). Used cooking oil can be processed into biodiesel as an alternative fuel, so it can be a source of additional income. This Community Service (PkM) activity aims to provide education about the dangers of used cooking oil for human health and the environment, as well as practice how to process used cooking oil into biodiesel for the women of the Al-Hijrah Ta'lim Assembly, Air Ali Hamlet, Negeri Rumah Tiga, Ambon. . The methods used in this PkM activity are lecture, demonstration and practice methods. All participants were very enthusiastic about participating in this PkM activity until the end. After following the education delivered by the lecturers, all participants became aware and aware of the dangers of used cooking oil for health and the environment. The participants were also very happy because they gained knowledge about how to process used cooking oil into biodiesel. This PkM activity has had a very positive impact on the surrounding community in Air Ali Hamlet.